1965
DOI: 10.1021/jf60139a009
|View full text |Cite
|
Sign up to set email alerts
|

Carbamate Insecticides, Effects of Chemical Structure on Intoxication and Detoxiation of Phenyl N-Methylcarbamates in Insects

Abstract: A further effect of the metabolism of the methylenedioxybenzenes at the site of insecticide metabolism could be the result of a nonspecific competition at some limiting step by the catechol derivatives resulting from reaction of the benzodioxolium ion with water.A combination of both of these suggested modes of inhibition is not unreasonable.The testing of methylene-deuterated methylenedioxybenzene synergists prepared in this laboratory is under way and preliminary data support the view that the synergistic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
1
1

Year Published

1977
1977
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 16 publications
5
49
1
1
Order By: Relevance
“…The compounds having the same linker between phthalimide group and phenyl group at the meta-postion were more potent than those substituted at ortho-position, which was different from the traditional carbamate insecticides [7,12,13]. The larger steric hindrance of ortho-alkyoxyl phthalimide than that of meta-position could cause the difference of activity from the traditional carbamate insecticides.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The compounds having the same linker between phthalimide group and phenyl group at the meta-postion were more potent than those substituted at ortho-position, which was different from the traditional carbamate insecticides [7,12,13]. The larger steric hindrance of ortho-alkyoxyl phthalimide than that of meta-position could cause the difference of activity from the traditional carbamate insecticides.…”
Section: Resultsmentioning
confidence: 82%
“…The larger steric hindrance of ortho-alkyoxyl phthalimide than that of meta-position could cause the difference of activity from the traditional carbamate insecticides. As the distance between the esteratic and anionic sites was 0.5 nm in the AChE molecule, carbamate insecticides would be most efficient if the distance between the two groups to be bound to the two sites of the enzyme was also 0.5 nm [7,12,13]. Compounds J1, J2 and K1-K8 showed higher activity than that of PDM, in which the substituents on the phenyl ring were longer than 0.5 nm to extent halfway into the gorge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of action of carbamate insecticides was that the carbamate part of the molecule was at- (6.19) tached to the esteratic sites, and the aromatic part (methyl) to the anionic sites of the AChE enzyme during the inhibitory process. As the distance between the esteratic and anionic sites was 0.5 nm in the AChE molecule, carbamate insecticides would be most efficient if the distance between the two groups to be bound to the two sites of the enzyme was also 0.5 nm, 9,13,14) but the substituents on the phenyl ring of compounds H1, H2, I1 and I2 were longer than 0.5 nm extending halfway into the gorge, which suggested that the phthalimide groups of these compounds interacted with other residues strongly lining the gorge.…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain inhibitors able to bind at the catalytic sites and the peripheral sites or at other sites on half of AChE, we designed molecules composed of two moieties (phthalimide and methylcarbamate) to bind at each site, linked by different carbon numbers of alkylene, and synthesized a series of novel phthalimide alkyloxyphenyl methylcarbamates. Carbamates with a protonated amine group in the middle of the chain were good AChE inhibitors but were incapable of reaching the action sites in the insect, because the nerve fibers are protected by a lipophilic sheath, 9) so the alkyloxy chains were selected as linkers.…”
Section: Introductionmentioning
confidence: 99%